PERSON-CENTERED APPROACH TECHNOLOGY FOR DEVELOPING SOCIO-COMMUNICATIVE COMPETENCE IN FUTURE TEACHERS (Scientific journal of the Fergana State University, 2025)
The article studies the issue of developing socio-communicative competence in future teachers based on a person-centered approach. The study analyzes the concept of socio-communicative competence, its components, and its role in pedagogical activity. The theoretical foundations, methodological principles, and practical mechanisms of the technology of a person-centered approach are identified, and their effectiveness in the process of training future teachers is substantiated. The work proposes ways to form social and communicative skills in students' activities through innovative methods, interactive teaching methods, and communicative training. The results of the study demonstrate the relevance and practical importance of a person-centered approach in the formation of this competence.